Mastering active server pages 3 - Jones, A. Russell (San Francisco, CA : SYBEX, 2000)
This book is divided into eight parts: Basic active server pages; Intrinsic ASP objects; Writing server-side code; Using components; Accessing databases with ASP and ADO; ASP applications; Advanced ASP; and Beyond ASP.
Keywords: Authorship; Internet programming; Internet programming; Web sites -- Authorship